Tideless estuaries in brackish seas as possible freshwater-marine transition zones for bacteria: the case study of the Vistula river estuary - Gołębiewski, Marcin; Całkiewicz, Joanna; Creer, Simon; Piwosz, Kasia (Environmental microbiology reports, 2017)
Most bacteria are found either in marine or fresh waters and transitions between the two habitats are rare, even though freshwater and marine bacteria co-occur in brackish habitats. Estuaries in brackish, tideless seas could be habitats where the transition of freshwater phylotypes to marine conditions occurs. We tested this hypothesis in the Gulf of Gdańsk (Baltic Sea) by comparing bacterial communities from different zones of the estuary, via pyrosequencing of 16S rRNA amplicons. We predicted the existence of a core microbiome (CM, a set of abundant OTUs present in all samples) comprising OTUs consisting of populations specific for particular zones of the estuary. The CMs for the entire studied period consisted of only eight OTUs, and this number was even lower for specific seasons: five in spring, two in summer, and one in autumn and winter. Six of the CM OTUs, and another 21 of the 50 most abundant OTUs consisted of zone-specific populations, plausibly representing micro-evolutionary forces. The presence of up to 15% of freshwater phylotypes from the Vistula River in the brackish Gulf of Gdańsk supported our hypothesis, but high dissimilarity between the bacterial communities suggested that freshwater-marine transitions are rare even in tideless estuaries in brackish seas.
Keywords: Sequence Analysis, DNA; Bacteria; sekvenční analýza DNA; společenstvo; DNA, Ribosomal; Seawater; mořská voda; sladká voda; RNA, Bacterial; RNA, Ribosomal, 16S; Estuaries; Fresh Water; RNA ribozomální 16S; Biota; bakteriální RNA; ribozomální DNA; estuár